2009
DOI: 10.1111/j.1365-2230.2008.02916.x
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis and risk factors in poor children from Great Buenos Aires, Argentina

Abstract: We found a high prevalence of AD in our study population. Not all the investigated risk factors for AD had a significant association with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
(63 reference statements)
0
9
1
1
Order By: Relevance
“…Contrary to other studies, 22,25 we found a similar proportion of male and female patients with eczema and there was no association between exposition to smoking and "severe eczema", "persistent eczema" or comorbidities. This lack of association to smoking exposition may be explained by a type II error because the sample is underpowered to detect the effects of smoking.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to other studies, 22,25 we found a similar proportion of male and female patients with eczema and there was no association between exposition to smoking and "severe eczema", "persistent eczema" or comorbidities. This lack of association to smoking exposition may be explained by a type II error because the sample is underpowered to detect the effects of smoking.…”
Section: Discussioncontrasting
confidence: 99%
“…21-24 These cohorts have shown the importance of particular risk factors and their influence in dermatitis, supporting the relevance of conducting this type of investigation worldwide. The prevalence of dermatitis varies among regions 10,25 and prospective cohort's studies in tropical regions as Latin America are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, of the studies that could have been relevant to our meta-analysis but were finally excluded, eight were discarded because they were an early version of cohort studies updated in subsequent publications [169][176]. Other studies published their results several times [175][181] in which case we chose to include the most complete report. Some studies were excluded because the outcome was not allergic rhinitis, dermatitis, or food allergy but rather SPT or IgE concentrations [182][192].…”
Section: Resultsmentioning
confidence: 99%
“…In the 0- to 6-year-old age group, only a history of raising pets was a significant variable among environmental factors. Environmental factors, such as secondhand smoking, curtains, carpets and moving to a newly built home before 1 year of age, were reported to be risk factors for atopic dermatitis [7,14]. Moving to a newly built home was reported to be consistently meaningful among environmental factors in recent studies in the Republic of Korea.…”
Section: Discussionmentioning
confidence: 99%